2018
DOI: 10.17583/mcs.2018.2749
|View full text |Cite
|
Sign up to set email alerts
|

Portrayals of Caring Masculinities in Fiction Film: The Male Caregiver in Still Mine, Intouchables and Nebraska.

Abstract: This article analyzes the male caregiving characters Driss in Intouchables (2011), Craig in Still Mine (2012) and David in Nebraska (2013) in terms of hegemonic masculinity and its variations (Connell 1990; Connell and Messerschmidt 2005). Caregiving is a complex social situation normally assumed within kinship relationships, and traditionally attributed to women. We briefly review feminist analysis of caregiving since the 1970s (Fine and Glendinning 2005), and use critical studies on men and masculinities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
2
0
4
Order By: Relevance
“…However, unlike their study that found career opportunities and salary as the most important motivators for entrance (Zamanzadeh et al, 2013, p.53), this study shows that desire to help people and satisfaction derived from the job have also been more important motivators for the male nurses. According to Araüna et al (2018), the ability to use and maintain a sense of humor in critical situations has been identified as a characteristic of male nurses. The caregivers in the study also exhibited similar conduct.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike their study that found career opportunities and salary as the most important motivators for entrance (Zamanzadeh et al, 2013, p.53), this study shows that desire to help people and satisfaction derived from the job have also been more important motivators for the male nurses. According to Araüna et al (2018), the ability to use and maintain a sense of humor in critical situations has been identified as a characteristic of male nurses. The caregivers in the study also exhibited similar conduct.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we made a close reading (Castelló, 2008) of the first season of the series. This technique is a method widely applied within cultural studies in the context of contemporary popular culture (Brummett, 2019;Castelló, 2008), and specifically for analyzing fiction series and films (e.g., Araüna et al, 2018;Fedele & Masanet, 2021). In this article, the analysis has been organized into four areas following previous studies carried out by the researchers of the project (Fedele & Masanet, 2021):…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, en ambas series, ellas son personajes fuertes, profesionalmente activos, que se alejan de las tramas adscritas a la esfera reproductiva, lo cual nos acerca a la reflexión de Galán (2007) sobre el movimiento inverso al que debería tender el hombre que cada vez más se representa en los personajes femeninos de la ficción española. Parece ser que las nuevas masculinidades emergen de manera natural en la esfera reproductiva, como feminización o alteración de la masculinidad que sigue presentándose como hegemónica (la arraigada a la ambición y el ejercicio de poder en el ámbito público); por ejemplo, la dificultad en representar al cuidador masculino sin recurrir al humor o las marcas de transgresión que analizan Araüna, Tortajada & Willem (2018). Estos personajes masculinos más igualitarios, permiten a su vez la mayor integración del personaje femenino que los complementa a la esfera laboral, pero en este desplazamiento mutuo lo que se aleja definitivamente es la posibilidad de visualizar como alternativa posible en la ficción contemporánea un modelo de corresponsabilidad en ambas esferas.…”
Section: Discusión Y Conclusionesunclassified